The Effect of Product Innovation and Sales Growth on Profitability in Technology Subsectors Listed on the Indonesia Stock Exchange, 2019-2023 - Iman Sobirin; Hariandy Hasbi (Dinasti Publisher, 2025)
Indonesia's digital economy is propelled by the technology industry, which demands ongoing innovation and adjustments to stay ahead. Within this intense competitive environment, profitability serves as the primary indicator of effective business strategies, highlighting the importance of examining key internal factors that influence profits for decision-makers. The objective of this investigation was to evaluate how product innovation and sales expansion affect profitability in 30 firms from the technology sub-sector traded on the Indonesia Stock Exchange over the period from 2019 to 2023. Employing a quantitative associative approach with secondary financial information, the study utilised multiple linear regression analysis on panel data spanning five years, combining cross-sectional and time-series elements. Results reveal that product innovation exerts a positive and meaningful influence on profitability, while sales growth demonstrates a positive yet statistically insignificant individual impact. Nevertheless, simultaneously these factors have a substantial joint effect on profitability, accounting for 48.2% of the variability. This work underscores the critical importance of innovative practices and strategies for market growth in improving the fiscal outcomes of technology companies in Indonesia. The outcomes are anticipated to guide leaders in enhancing R&D expenditures and fostering enduring sales development.